Pengaruh Gaya Belajar Terhadap Hasil Belajar Siswa [The Influence of Learning Styles on Student Learning Outcomes] - Sugiarto, Antonius; Erawati, Erawati; Soelaksono, Tri Poedji (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2024)
Learning style refers to the way a person or student acquires knowledge taught by a teacher in the classroom. Each student has a different learning style. Some students may have only one learning style, while others may have several. Given the diversity of learning styles, this research aims to investigate whether a student's learning style can influence their academic achievement. A Likert scale questionnaire with four indicators was used as a research instrument to measure the learning styles of the students. In addition, a chi-square (X²) test was conducted to determine if there is a relationship between learning styles and academic achievement, and a mean test was used to determine if one particular learning style has a greater impact on academic achievement. The data analysis using the chi-square test showed that H0 was accepted, meaning there is no significant relationship between students' learning styles and their academic achievement. The mean test also showed that H0 was accepted, with the calculated F-value (1.16) being greater than the tabulated F-value (0.84).